The Prevalence of Cyclospora cayetanensis and Cryptosporidium spp. in Turkish patients infected with HIV-1 - YÜKSEL MAYDA, PELİN; Uysal, Hayriye Kirkoyun; Adas, Gokhan Tolga; Atalik, Kevser; Altiparmak, Semih; Akgul, Ozer; Saribas, Suat; Gurcan, Mert; Yuksel, Pelin; Yildirmak, Taner; Kocazeybek, Bekir; Ziver, Tevhide; et al. (My University, 2017)
Opportunistic infections such as cryptosporidiosis and cyclosporiasis are commonly encountered in patients with acquired immunodeficiency syndrome (AIDS). We investigated the existence of opportunistic protozoans that significantly affect the quality of life in HIV-1 infected patients using conventional and molecular methods. The study group comprised 115 HIV-1 positive patients. In the identification of Cyclospora cayetanensis and Cryptosporidium, the formol-ether precipitation method was used and smears were evaluated in optical microscope by staining modified Ziehl-Neelsen (ZN). The primers and probes used for PCR were Heat shock protein 70 for C. cayetanensis and the oocysts wall protein for Cryptosporidium spp.. Cyclospora and Cryptosporidium spp. oocysts were detected in one and two patients, respectively, by staining, whereas we detected C. cayetanensis in three patients out of 115 (2.6%) by PCR, and Cryptosporidium spp. in a further three patients (2.6%). C. cayetensis was detected in patients with CD4 counts of 64 cells/mu m, 182 cells/mu m and 287 cells/mu m, respectively. Cryptosporidium spp. was detected in patients with CD4 counts of 176 cells/mu m, 241 cells/mu m and 669 cells/mu m. As conclusion, PCR method is faster and more sensitive than microscopic methods and to screen intestinal pathogens routinely in patients infected with HIV should not be neglected in developing countries like Turkey.